2014
DOI: 10.4187/respcare.03075
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Application of Oxygen Therapy Via High-Flow Nasal Cannula and Noninvasive Ventilation in Acute Respiratory Failure: An Observational Pilot Study

Abstract: BACKGROUND:The aim of this study was to evaluate the clinical efficacy of humidified oxygen via high-flow nasal cannula (HFNC) alternating with noninvasive ventilation (NIV) in acute hypoxemic respiratory failure (AHRF). METHODS: We performed a prospective observational study in a 12-bed ICU of a university hospital. All subjects with a P aO 2 /F IO 2 of < 300 mm Hg with standard mask oxygen and a breathing frequency of > 30 breaths/min or signs of respiratory distress were included and treated with HFNC first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
2
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 26 publications
6
156
2
6
Order By: Relevance
“…In a pilot study successively assessing standard oxygen, HFNC and NIV in patients with ARF, PaO 2 increased from standard oxygen to HFNC without changes in PaO 2 /FiO 2 ratio (17). This suggests that oxygenation improvement was mainly due to increased FiO 2 .…”
Section: Oxygenation and Peep Effectmentioning
confidence: 90%
See 2 more Smart Citations
“…In a pilot study successively assessing standard oxygen, HFNC and NIV in patients with ARF, PaO 2 increased from standard oxygen to HFNC without changes in PaO 2 /FiO 2 ratio (17). This suggests that oxygenation improvement was mainly due to increased FiO 2 .…”
Section: Oxygenation and Peep Effectmentioning
confidence: 90%
“…However, clinical studies have shown less improvement in oxygenation with HFNC than with NIV, probably due to lower impact of the PEEP effect with HFNC than with NIV (10,17). In a pilot study successively assessing standard oxygen, HFNC and NIV in patients with ARF, PaO 2 increased from standard oxygen to HFNC without changes in PaO 2 /FiO 2 ratio (17).…”
Section: Oxygenation and Peep Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the establishment of the new definition of ARDS in 2012, the concept of initiating therapeutic interventions according to disease severity was introduced,35, 185 and numerous reports have been made in recent years describing the clinical utility of techniques such as oxygen therapy in mild ARDS cases, oxygen therapy administered via high‐flow nasal cannula (high‐flow nasal therapy), and noninvasive positive pressure ventilation 186, 187, 188, 189. Administering oxygen in some form to sepsis patients presenting with hypoxemia is widely practiced, and while this approach is believed to help prevent the onset of acute respiratory failure leading to ARDS, there is currently no clear supporting evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The hazard ratio for death at 90 days was 2.01 (95% confidence interval (CI), 1.01 to 3.99) with standard oxygen versus high-flow oxygen (p=0.046) and 2.50 (95% CI, 1.31 to 4.78) with NIMV versus high-flow oxygen (p=0.006).Intubation rates were not significantly different among three groups (38% in the high flow O 2 group, 47% in the low flow O 2 group and 50% in the NIMV group [11].A prospective trial in patients with hypoxemic respiratory failure, HFOS applied sequentially with non-invasive mechanical ventilation (NIMV) and shown that HFOS improved oxygenation but not as much as NIMV compared to standard oxygen therapy [12].…”
Section: High Flow Oxygen Systemmentioning
confidence: 99%